A Rare Pediatric Case of Dengue Hemorrhagic Fever with Encephalopathy and Suspected Subdural Hemorrhage - Aulia Cempakasari; Tiara Rahmawati; Alief Qobidh Al Bashor Arifin; Dewi Syahputri; Firdha Yekti Hutami; Renata Prameswari; Pramita Anindya Nugraheni; Ronald Pratama Adiwinoto; I Made Dwi Mertha Adnyana (Asian Journal of Health Research, 2025)
Introduction: Dengue Hemorrhagic Fever (DHF) is a severe arboviral infection that rarely leads to neurological complications. Dengue encephalopathy, often secondary to metabolic disturbances or shock, presents a significant diagnostic and management challenge in the pediatric population. Case Presentation: We report the case of a 4-year-3-month-old obese girl presenting with fever, gastrointestinal symptoms, and progressively decreasing consciousness (apathetic). Diagnosis of DHF was confirmed by a positive NS1 antigen test, severe thrombocytopenia (nadir 14,000/µL), and hemoconcentration with pleural effusion. Hepatic involvement was noted (SGOT 117.81 U/L). Neurological involvement was characterized by clinical encephalopathy, and a head CT scan revealed hyperdense lesions suspecting subdural hemorrhage (SDH). The patient required multidisciplinary management in the Intensive Care Unit (ICU) for supportive fluid therapy, inotropic support (Dobutamine), and platelet transfusion. The patient showed marked clinical improvement and was discharged on day nine. At a two-week post-discharge follow-up, she demonstrated full cognitive and motor recovery with no neurological sequelae Conclusion: This case highlights the critical need for clinical vigilance for rare, simultaneous neurological complications (encephalopathy and suspected SDH) in pediatric DHF. It underscores that early diagnosis and aggressive, multidisciplinary supportive care can lead to complete recovery even in severe presentations.